Relationship between Smoking and Hereditary with Hypertension - Suprapto, Suprapto; Mulat, Trimaya Cahya; Norma Lalla, Nur Syamsi (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2021)
Smoking describes overt behavior where smokers inhale tobacco. High blood pressure describes the condition of systolic blood pressure â‰¥140 mmHg and diastolic â‰¥ 90 mmHg at 2 times checking blood pressure measurements within 5 minutes duration in calm conditions. This type of research is an observational analytic method with a cross-sectional approach. Sampling using is a purposive sampling method. Data were analyzed by Chi-Square Test. Using Chi-Square test analysis prove p-value = 0. 016 which is less than the significance value (0.05), proves that there is an important relationship between smoking habits with high blood events and there is a relationship between the generation aspect and high blood events and by using the Chi-Square test proves p-value = 0. 023 were less than the significance value (0.05). There is a link between smoking and the history of generation to the hypertension event in the area of the Makassar City Health Center of Barombong. It can be applied by respondents and families in helping to lower blood pressure in an efficient and efficient way by avoiding aspects that can be replaced.